Palladacycles for directed and nondirected C H bond functionalization of (Hetero)arenes - Soni, Vineeta; Punji, Benudhar (Strategies for palladium-catalyzed non-directed and directed C-H bond functionalization, 2017)
Application of palladacycle complexes in catalytic organic transformation is rapidly expanding. This chapter is mainly focused on the use of palladacycle precatalysts in CH bond functionalizations, as well as an overview of palladacycle intermediates in directed CH bond functionalization reactions. The described palladacycle precatalysts are more efficient and more selective than the traditional palladium complexes for CH bond functionalization processes. The second part of the chapter summarizes the involvement of palladacycle intermediates in various directed CH bond functionalizations that are proposed with experimental evidence. Some of the palladacycle intermediates described are shown to be competent as catalyst precursors. It has been demonstrated that the formation of palladacycle (precatalyst or intermediate) makes the CH functionalization process more facile, because of the high stability associated with palladacycles.